Aptamers: Biomedical Interest and Applications - Cristina Romero-López; Alfredo Berzal-Herranz (Pharmaceuticals, 2017)
Aptamers are short DNA or RNA oligonucleotides specialized in the specific and efficient binding to a target molecule. They are obtained by in vitro selection or evolution processes. It was in 1990 that two independent research groups described the bases of a new in vitro technology for the identification of RNA molecules able to specifically bind to a target [1,2]. Tuerk and Gold established the principals of the in vitro selection process that was named SELEX (Systematic Evolution of Ligands by Exponential enrichment), which is based on iterative cycles of binding, partitioning, and amplification of oligonucleotides from a pool of variant sequences [2]. Ellington and Szostak coined the term aptamer to define the selected molecules by the application of this method [1]. To date, numerous reports have described the isolation of aptamers directed against a great variety of targets covering a wide diversity of molecules varying in nature, size, and complexity ranging from ions to whole cells, including small molecules (e.g., aminoacids, nucleotides, antibiotics), peptides, proteins, nucleic acids, and viruses, among others (for example, see [3–6]). Modifications and optimization of the SELEX procedure aimed to get newly modified aptamers has also attracted much interest (examples can be found in [7,8]). These advances along with the parallel progresses in the nucleic acids chemistry and cellular delivery fields have allowed for the rise of a new hope in developing aptamers as efficient molecular tools for diagnostics and therapeutics (for recent comprehensive reviews, see [9–11]).